Professional Identity of Young Teachers in the Structure of the Regional Educational Cluster - Svetlana Mazanova; Elena I. Mychko; Anna Serykh; Elena Potmenskaya (ARPHA Proceedings, 2022)
The development of a young teacher is always associated with the formation of the professional identity. This process is considered to be a long-term, complex and dynamic. There is a need for an organizational and substantive study of the resource provision of the process of forming the professional identity of young teachers.In this regard, the problem of our research is that it is necessary to develop the professional identity of young teachers in the conditions of a regional educational cluster. This has allowed us to formulate the goal of our research. The purpose of the study is to substantiate the systemic and functional capabilities of the regional educational cluster in the development of the professional identity of teachers.In order to test the hypothesis about the systemic and functional capabilities of the regional educational cluster, such methods as theoretical (this is the analysis of scientific literature on the problem of developing the professional identity of young teachers; studying and summarizing the experience of creating an educational cluster), empirical (this is the observation, survey and testing) and methods of mathematical processing of the obtained data were used.The empirical study was carried out on the basis of secondary schools in the city of Kaliningrad, which are the subjects of the regional educational cluster. In the process of diagnostics, we have studied the following: the formation of the self - awareness as a subject of the professional interaction; understanding the value of the profession as an important component of life-meaning orientations and readiness to independently implement the strategy of professional self-determination and development.The obtained results can be useful to the specialists in the field of management in the design of educational projects that are aimed at improving the professional activities of young teachers.